A Retrospective Study on English Teachers’ Strategies to Improve Students’ Writing Skills - Panjaitan, Elisabeth Indah Natalia; Lius, Novita Cuan; Saragih, Erikson (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Writing is the act of conveying thoughts, facts, knowledge, or understanding for further study or to communicate and absorb certain information. Writing can be used to express art or beauty as well as words. Everything that is put into writing, including memories, folklore, and imagination, can then be integrated into a publishable narrative. Despite the fact that teachers in Indonesia have done a lot of research on writing skills, there is currently little literature on the writing tactics teachers use to help students develop their writing skills. The purpose of this study was to learn more about the tactics teachers use when teaching students in writing, including how to evaluate student progress. Qualitative data analysis approach is used to analyze research data. Specifically, collecting data, reducing it, analyzing it, and drawing conclusions. This study uses a qualitative methodology with a survey design. Ten English teachers from Medan participated in the study as participants. The findings show that instructors make extensive use of a variety of strategies, including exercises and writing assignments. Of the two, the teacher believed that practice was the most successful in helping students improve their writing skills. Studying a lot of things around can also affect it, such as remembering vocabulary around the environment and writing it down according to the existing reading provisions.